The Impact of Tourism in East Africa A Ruinous System - Storch, Anne (Tourism and Cultural Change, 2021)
This book explores the relationship between imperial formations and individual encounters at African tourist sites - spaces of leisure, healing and work. It examines how encounters between tourists and hosts tend to be constructed along colonial thought lines and considers how players in the hospitality industry do not interact as coeval participants, but are racialised, scripted and positioned according to colonially-established order. The authors focus on the language of these encounters, not only speech, performance and response, but also silence, resonance, emptiness, noise - objectified, materialised, evasive and confusing. Through its exploration of language in these encounters, the volume shows that ruination is the one feature that is omnipresent in the multiple and diverse tourist settings of the postcolonial world. This book is open access under a CC BY ND licence.